Observations on the growth in vitro of myeloid progenitor cells and fibroblasts from hemizygotes and heterozygotes for “complete” and “partial” hypoxanthine-guanine phosphoribosyltransferase (HGPRT) deficiency, and their relevance to the pathogenesis of brain damage in the Lesch-Nyhan syndrome - McKeran, R.O.; Howell, A.; Andrews, T.M.; Watts, R.W.E.; Arlett, C.F. (Journal of the neurological sciences, 1974)
1. (1) Brain and bone marrow are similar, in that they both depend heavily on the purine salvage pathways (catalysed by purine phosphoribosyltransferases), rather than on de novo purine biosynthesis for the supply of ribonucleotides. 2. (2) Myeloid progenitor cells from affected hemizygotes with either the complete, or partial deficiency of hypoxanthine guanine phosphoribosyltransferase (HGPRT) produced fewer, and in the complete deficiency, smaller cell colonies than normal controls when cultured in agar. Conversely, the ability of fibroblasts from these patients to proliferate in vitro was not detectably different from that of the fibroblasts from control normal subjects. 3. (3) Myeloid progenitor cells from heterozygotes for the complete deficiency of HGPRT produced normal numbers of cell colonies when cultured in agar. Conversely, myeloid progenitor cells from a heterozygote for incomplete deficiency of HGPRT produced fewer colonies than controls. 4. (4) Measurement of the ratio of the activity of HGPRT to adenine phosphoribosyltransferase (APRT) in single bone marrow colonies derived from a heterozygous carrier for the complete HGPRT deficiency showed only a small proportion (2 out of 17 colonies) without detectable HGPRT. Equal numbers of HGPRT-positive and HGPRT-negative colonies would be predicted on the basis of the Lyon hypothesis of random X-chromosome inactivation. The reasons for this finding are discussed. 5. (5) The relevance of the present observations to the pathogenesis of brain damage in the Lesch-Nyhan syndrome, which is associated with complete or almost complete HGPRT deficiency is discussed.